Mapping of the interraction between multivalent transcription factor, ctcf and y box binding protein 1 (yb-1) in glioma and osteosarcoma cell lines - Shamsuddin, Shaharum (Pusat Pengajian Kesihatan, 2016)
CTCF is an 11-Zn finger transcription factor, involved in the regulation of transcription, insulator function, control of imprinting and the X-chromosome inactivation. CTCF is ubiquitously expressed and it is highly conserved between the species. Identification of proteins interacting with CTCF can help to understand the biological function of CTCF in the cell. Previously reported studies have identified numerous CTCF protein interacting partners and two of the protein partners were chosen for this study. The first protein was the transcription factor YB-1, a member of the Y-box family and the second protein was the Large Subunit of RNA Polymerase II (LS Pol II), the principal enzyme for transcription. The interaction of CTCF and YB-1 was characterized in the Glioma- RGBM cell line. The co -IP results showed that CTCF was able to form a complex with YB-1 in the RGBM total cell lysate. The interaction between these two proteins was further characterized through in vitro pull-down assay. From the results obtained, CTCFZF was the only domain binds with YB-1 CSD. The rest of domains did not show any interaction. Next, the significant of functional interaction between these two transcriptional factors was determined via mammalian two-hybrid system. The results showed a strong interaction between CTCF and YB-1 when both were co-transfected into RGBM cell line which proved the biological significant of these two proteins interaction in the cell.